FEMALE CRIME IN FAR EAST OF RUSSIA - Oksana Ilchenko (European Scientific Journal, ESJ, 2014)
Most national and international research in the area of violent crime directed at the study of men. However, crime committed by women, is recognized as a serious criminological and social problem in Russia. Usually women are associated with a special volume in the society; they gave great influence to family and children. That is why female crime (especially violent) remains a matter of surprise, suspicion and is considered as abnormal behavior. In this paper, based on empirical research we want to show some tendencies of female crime. Official statistic of the Federal Penal Service was analyzed and also we use the results of empirical study conducted in the penal colony of Vladivostok. The survey had place in March 2013. Total 212 women from 18 to 64 years old were attended.